Computerised methods for animal health risk assessment using the EPIZOO 2.6 program - Kouba, V (Revue scientifique et technique (International Office of Epizootics), 1997)
A computerised set of methods for the risk assessment of infectious diseases has been developed as part of a software package which deals with animal population health and disease analyses and programming (EPIZOO, version 2.6). This set includes methods for calculating the following: general indicators of risk of animal disease. Risk probability assessment of propagation of disease. Risk probability assessment of the introduction of disease through the importation of animals and their products, based on predefined criteria and on non-predefined criteria. Risk comparison of the introduction of one disease agent from several territories. Risk comparison of the introduction of several disease agents from one territory. Risk of disease propagation related to the movement and concentration of the animal population. Risk of disease propagation related to the transfer of animal products. Risk of the probability of negative test results in infected animals. Risk of the probability that at least one imported animal or animal product unit is infected.
Keywords: infekční nemoci; obchod; software; Commerce; Risk Assessment; Animals; Risk Factors; Probability; pravděpodobnost; rizikové faktory; hodnocení rizik; Software; zvířata; Communicable Diseases